Actualizing the objective of National Philosophy of Education through group learning: a case study - Hassan, Aminuddin (The Journal of Human Resource and Adult Learning, 2009)
This research is conducted to identify the perceptions of rural area students toward the implementation of group activities within English lessons as the second language where it focuses on six queries; what are the perceptions of students toward group activities within English lessons, is group activity approach the learning technique that motivate students to learn English better, is it the technique of group learning that makes students diligent to learn English, is the increase in achievement in the English subject resulted from the application of group learn ing technique in students’ learning process, is there any difference in perceptions toward group learning technique within English lessons, and is there any difference of perceptions between male and female student s toward group learning technique within English lessons. Descriptive design has been used in the study where results show that students enjoy the learning process more by learning in groups and they found that group work activities are beneficial in increasing their motivation to learn and enc ourage them to study English more attentively. Moreover, results obtained also show that students’ English achievement increases after experiencing group learning activities.